Analysis of cultural policies in Peru - Pino Apablaza, Fernando (2021)
The investigation was donde in Lima city, in the first trimester of 2021. Had like objectives: conceptualize the policy, the culture, and cultural policies. Also, identify the main problematics about the cultural policies in the governmental administration, describe the peruvian laws about the culture, propose the culture like a development factor and finally, describe a taxonomy about the cultural and creatives industries. The objectives of investigation were done, through the documental analysis. Finally the conclusion was that the cultural public policies are incipient and weaks. And the authorities on duty, dont put the right atention and importance, considering the cultural points like something in second stage in the community development.